Pengaruh Kualitas Audit dan Keberadaan Eksekutif Wanita terhadap Earnings Management dengan Tax Avoidance sebagai Pemoderasi - Ayu Oktaviani; Vinola Herawaty; Nurul Tri Wulandari (LITERATUS, 2022)
This study aims to examine and analyze the effect of Audit Quality and the Presence of Female Executives on Earnings Management with Tax Avoidance as a moderating variable and Leverage as a control variable. One of the components of information in financial statements is information about company profits. Earnings management problems arise because of agency problems caused by the separation of roles or differences in interests between company owners (shareholders) and company managers (management). Management acts as the manager of the company having information about the company faster, and more valid than the shareholders (information asymmetry) so that it causes management to carry out accounting practices oriented to profit figures, which can create a certain impression (achievement). Toshiba Corp is one case of opportunistic earnings management. This study uses a sample of all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the period 2017 – 2020. The technique used in data collection is purposive sampling and the method used in analyzing the research is multiple regression analysis with moderation. The results obtained are Audit Quality and the Presence of Female Executives proven to be able to influence Earnings Management. Meanwhile, Tax Avoidance has been proven to be able to weaken the influence of the Presence of Female Executives on Earnings Management. However, Tax Avoidance is not proven to be able to weaken the influence of Audit Quality on Earnings Management. In addition, Tax Avoidance is also not proven to have an effect on Earnings Management.